Structural Carbon and Compartments in Forests Certified by the Forest Stewardship Council, in Oaxaca, Mexico - Espinoza-Zúñiga, Pablo; Leos-Rodríguez, Juan Antonio; Rodríguez-Ortiz, Gerardo; Montiel-Batalla, Blanca Margarita; Valdivia-Alcalá, Ramon (Ecosistemas y Recursos Agropecuarios, 2023)
This study compares the amount of structural and aboveground compartment carbon (C) versus soil C under two silvicultural treatments (ST) - thinning and regeneration cut. Measurements were made in 2021 at sampling sites (SS) located in Oaxaca, Mexico, corresponding to a community certified in forest management practices by the Forest Stewardship Council, versus a non-certified forest community. Analysis of variance and tests of means were performed under a completely randomized design with factorial arrangement and cluster analysis of the SS. No differences by community or ST by themselves are documented, but the interaction between community and ST generated highly significant effects (p ≤ 0.01), in such a way that the SS in the certified community presented higher amounts of C in the evaluated compartments. The ST thinning in SS of the certified community generated higher C content in trees and forest floor than in SS of the community without certification (334% and 24%, respectively). The SS with regeneration cuts, certified or not, increase C by 120.2%, by incorporating the amounts stored in the C fixed in the tree into the forest floor. There were no differences in the C stored in the forest floor between communities (165.97 tC ha−1 ), regardless of the ST applied. The results are useful for decision-making by designers of public policies aimed at improving forest management, which have an influence on the amounts of C stored in the ecosystem.